Hybrid Algorithm for Distribution of Nodes Using Vanets Networks - Kasani Vaddi Kasulu; Raavi Satya Prasad (Revista Electronica de Veterinaria)
Today wireless services are the most preferred services in the world and the ultimate goal become to communicate any type of information with anyone, at any time, from anywhere, with no need for conductors or wires. Based on the capacity the cellular networks are improving year by year. Nowadays 5G networks are most widely used by many mobile operators to increase performance in terms of increased data rate, reduced latency, and provide the best quality of service. In this paper, a dynamic data transfer protocol in VANETs is developed to transfer the data without any fluctuations or data loss. The main focus of this approach is to provide the data transfer service with high speed and maintain intelligent routing to reach the destination without any loss. Every node in the algorithm maintains the buffer storage to transfer the data in peak hours. This is the combination of Packet data convergence protocol (PDCP) and the dynamic routing protocol to provide Quality of Service (QoS) in wireless 5G networks. Providing network connectivity to mobile users is a key requirement for cellular wireless networks. User mobility impacts network performance as well as user-perceived service quality. The performance of the proposed approach is measured by using Packet Delivery Ratio (PDR), Packet Loss (PL), Throughput, and network delay.